Identification of biomarkers related to metabolically healthy or unhealthy obesity in children and adolescents with depressive disorders: a cross-sectional study - Zhiwei Liu; Liang Sun; Fengshun Li; Tengjiao Liu; XingLong Yin; Jingjing Zhang; Nana Sun; Yulong Zhang; Gaofeng Yao; Yun Liu (Scientific Reports)
Abstract Obesity now stands as a paramount public health challenge globally. The classification of individuals with obesity extends into two categories: those with metabolically healthy obesity (MHO) and those with metabolically unhealthy obesity (MUO), differentiated by the presence or absence of metabolic irregularities. This study aimed to explore the independent correlates of MHO or MUO in children and adolescents with depressive disorders. In a study conducted at the Third People’s Hospital of Fuyang throughout 2021, 515 pediatric adolescent in-patient patients diagnosed with depressive disorders according to the ICD-10 criteria were examined. Comprehensive demographic and clinical data were gathered for these individuals. Using regression analysis, the research delved into the distinct impacts of MHO and MUO on these patients. This approach aimed to discern the varying contributions of metabolic health statuses to depressive symptoms in this demographic group. The detection rates of MHO and MUO were 3.7% (19/515) and 8.0% (41/515), respectively. Compared with the MHO group, patients in the MUO group showed older age, older ages of onset and first hospitalization of depressive disorders, higher systolic and diastolic blood pressure, higher levels of TG, TC/HDL, TG/HDL, TyG index and AST, and lower levels of HDL. Binary regression analysis showed that a high level of LDL (OR = 2.76, P = 0.007) was an independent risk factor for MHO, whereas older age at the onset of the disorders (OR = 0.69, P = 0.002) was a protective factor for MHO. In addition, high levels of TC/HDL (OR = 2.66, P = 0.003), TG/HDL (OR = 1.81, P = 0.034), AST (OR = 1.03, P < 0.001), and uric acid (OR = 1.004, P = 0.018) were independent risk factors for MUO. Children and adolescents suffering from depressive disorders exhibit increased rates of both MHO and MUO. It is imperative in clinical settings to monitor these conditions closely. Proactive measures are essential to address the underlying risk factors, thereby mitigating the progression from MHO to MUO and enhancing patient outcomes.